Effects of inspiratory muscular training on inspiratory muscle performance in a patient with congenital muscular dystrophy with mersosine deficiency: a case report (Research, Society and Development, 2021)
Congenital muscular dystrophy with merosin deficiency (MDC1A) is characterized by an impairment of muscle fiber by partial or complete deficiency of α2 laminin, (merosin) an extracellular protein responsible for maintaining cellular structure. Biomechanical changes in the structures involved with the respiratory act can trigger respiratory muscle weakness and low resistance to fatigue, showing respiratory distress and other worsening lung function. In response to this, the effects of respiratory muscle training (RMT) have been explained over the years in the literature. Although the benefits of RMT are known, there is no defined consensus regarding protocols and type of RMT to be used in patientes with neuromuscular disorders, especially in children, due to the scarcity of studies conducted with this specific group of patients. Therefore, the presente study aims to determine the effects of a RMT protocol on respiratory muscle strength and peak expiratory flow of a patient with congenital muscular dystrophy with merosine deficiency.